A=2 (5-3y) + 2y - (2y+5) x 3
B = 3z - 2 (-4z +8) - 4 (3z-1)
C = 3- (-5x+4) + 2x (-3x+9) + 2x au carré
D = 4+2 (3t + 5) + 3t2 ( 4) - (2t +5) x 3

J'ai terminé mes exercices, mais j'aimerais savoir si c'est bon avant de mettre au propre.
Merci à vous.

1

Réponses

  • Utilisateur Brainly
2013-12-06T13:42:24+01:00
A=2 (5-3y) + 2y - (2y+5) x 3
  =10-6y+2y-6y-15
  =-10y-5

B = 3z - 2 (-4z +8) - 4 (3z-1)
   =3z+8z-16-12z+4
   =-z-12

C = 3- (-5x+4) + 2x (-3x+9) + 2x²
   =3+5x-4-6x²+18x+2x²
   =-4x²+23x-1

D = 4+2 (3t + 5) + 3t2 ( 4) - (2t +5) x 3

   =4+6t+10+12t²-6t-15
   =12t²-1